From the history of the Department of Mathematics at the Agricultural University of Lithuania - Kaminskienė, Janina; Liubertienė, Janina (Lietuvos matematikos rinkinys, 1999)
The article is dedicated to the 50 years anniversary of the Mathematics Department. The foundation’s history is described there. All the heads of the Department and their biographies are mentioned in this article. The main directions of scientific work and methodical work are analysed.